Characterization of the Volatile Components of Essential Oils of Selected Plants in Kenya - Mugao, Lydia G.; Gichimu, Bernard M.; Muturi, Phyllis W.; Mukono, Simon T. (Hindawi, 2020)
Essential oils are secondary metabolites that plants produce for protection from pests and predators, attraction of pollinators, and seed dispersal. )e oils are made up of a mixture of compounds that give a characteristic flavour and odour. Currently, essential oils are receiving great attention in research for their phytochemical and antimicrobial activities. However, there is scanty information on the chemical composition of many plants. )is study provides a detailed analysis of the chemical composition of essential oils of ginger, garlic, tick berry, and Mexican marigold in Kenya. )e essential oils were extracted by steam distillation and analysed by gas chromatography–mass spectrometry. )e study identified a total of 52 different chemical classes from the essential oils of the four different plants that were analysed. )eir percentage composition was also found to vary between the test plants. )e essential oils of Mexican marigold constituted the highest composition of the identified chemical classes at 71.2%, followed by ginger at 55.8%, while both tick berry and garlic oils constituted 53.8% of the total classes identified. Terpenes constituted the highest composition in the essential oils of all the four test plants. Other major chemical classes included esters, ketones, organosulfurs, alkanes, cycloalkanes, steroids, aromatic hydrocarbons, and alkanols. Some of these chemical compounds have been shown to have a huge utility potential in biopesticides, pharmaceutical, and food industries, and hence, their industrial extraction and purification from the essential oils of these plants are recommended.